THE CURRENT STATE OF ACTIVITY AND STATE POLICY IN THE ECONOMIC DEVELOPMENT OF BUSINESS ENTITIES IN THE SERVICE SECTOR - Karimova Aziza , Makhomadrizoevna (THE INNOVATION ECONOMY, 2025)
This article discusses issues related to the study of the current state of government activity and policy in the economic development of business entities in the service sector. The regulatory legal acts adopted by the state of the country are outlined, an analysis of GDP production by type of economic activity is carried out, the volume of key indicators of business entities by economic sectors, conclusions are drawn and proposals are made to further improve the industry